(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Katarina Bogdanović (1885-1969) was a philosopher, educator, writer, literary critic, literary historian, and the first woman in Serbia who, along with Paulina Lebl-Albala, wrote a high school textbook. She is one of the most important women in the history of Kragujevac, as well as one of the most prominent intellectuals at a time when few women found the courage and strength for intellectual growth and social activism through public action and involvement in the movements that represented resistance to violence and discrimination against women. This paper is written from the perspective of women’s historiography, using primary and secondary historiographical methods. It analyzes Katarina Bogdanović’s life path, from a social outsider (from the perspective of gender and her belonging to the lower social class) to someone at the top of the professional pyramid (she was one of the two first women principals of secondary schools in Serbia). Katarina Bogdanović emphasized freedom of choice as the main parameter of success.